FRAUD DETECTION IN ISLAMIC BANKING: THE INTERPLAY OF ETHICS AND GOVERNANCE - Odhi Pratama; Andreas; M Rasuli (Universitas Riau, 2026)
This study examines the effects of workplace spirituality, role stress awareness, and audit communication quality on fraud detection, while investigating the moderating roles of Islamic organizational culture and whistleblowing climate in Islamic banking. Prior research has largely examined behavioral and organizational factors separately, providing limited understanding of how these dimensions jointly influence fraud detection. A quantitative research design was employed using a census of 62 Internal Auditors and Quality Control personnel at Bank Riau Kepri Syariah. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that workplace spirituality, role stress awareness, and audit communication quality positively influence fraud detection. Islamic organizational culture moderates only the relationship between workplace spirituality and fraud detection, whereas whistleblowing climate moderates the relationships involving workplace spirituality and role stress awareness. However, neither moderator influences the relationship between audit communication quality and fraud detection. This study extends Attribution Theory by integrating behavioral and organizational determinants within a unified fraud detection framework in Islamic banking. The findings provide practical implications for strengthening anti-fraud governance through ethical values, role stress management, effective audit communication, Islamic governance, and credible whistleblowing mechanisms.